PENGARUH MODEL PEMBELAJARAN 3CM (COOL-CRITICAL-CREATIVE-MEANINGFUL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Dhea Ayu Devi Mayang Sari; Miftahir Rizqa (Universitas Batanghari Jambi, 2026)
This research aimed at describing the effect of 3CM learning model toward student mathematical problem-solving ability. Quasi-experimental method was used in this research with non-equivalent posttest-only control group design. This research was conducted at State Junior High School 2 Siak, the eighth-grade students of class 2 were the experimental group, and the students of class 3 were the control group. The technique of analyzing data was t-test. The research findings showed the mean difference in t-test that the experimental group was better than the control group. Therefore, it could be concluded that there was an effect on mathematical problem-solving ability between students taught by using 3CM learning model and those who were taught by using conventional learning. 3CM learning model had a positive impact on mathematical problem-solving ability. 3CM learning model could be used as an alternative to increase student mathematical problem-solving ability on One Variable Linear Equations and Inequalities material.